THE EFFECT OF COMPENSATION, LEADERSHIP STYLE AND WORK DISCIPLINE ON THE PERFORMANCE OF HOSPITAL EMPLOYEE IN UNITED STATES - Andres Rodriguez-Clare; Jonathan Dingel (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
This study aims to find out how InfluenceCompensation, Leadership Style and Work Discipline on the Performance of Hospital Employee In United States. Therefore the author is interested in taking the title "The Influence of Compensation, Leadership Style and Work Discipline on the Performance of Hospital Employee In United States. The results of testing the hypothesis using multiple regression analysis and t test show that: a ttable value of 2.048 is obtained. From this description it can be seen that tcount (2.591) > ttable (2.048), likewise with a significance value of 0.01< 0.05 then it can be concluded hypothesisfirst received, that is Compensation Variable (X1)positive and significant effect on Employee Performance Variable (Y).A ttable value of 2.048 is obtained. From this description it can be seen that tcount (0.016) < ttable (2.048), likewise with a significance value of 0.98> 0.05 it can be concluded hypothesisboth rejected, meaningLeadership Style Variable (X2) has no effect on Employee Performance Variable (Y).A ttable value of 2.048 is obtained. From this description it can be seen that tcount (1.257) < ttable (2.048), and a significance value of 0.22 > 0.05, it can be concluded that the third hypothesis is rejected, meaningWork Discipline Variable (X3) has no effecton Employee Performance Variable (Y). The Ftable value of 2.98 is obtained. From this description it can be seen that Fcount (9,470) > Ftable (2.98), and a significance value of 0,00<0.05, it can be concluded that the fourth hypothesis is accepted, meaning that the Compensation Variable (X1), Leadership Style Variable (X2) and Work Discipline Variable (X3) have a positive and significant simultaneous effect on Work Discipline Variable (Y)